Takotsubo cardiomyopathy associated with adrenal insufficiency in the context of long-term steroid use mimicking acute coronary syndrome. Issue 1 (25th January 2021) - Bagnall, Timothy; Tow, Ying Ran; Bunce, Nicholas; Astroulakis, Zoe
Abstract : Takotsubo cardiomyopathy (TCMP) is an important, though under-recognised, syndrome which mimics acute coronary syndrome (ACS) presenting with similar clinical, biochemical and ECG features. A 68-year-old man was referred as ACS for emergency coronary angiography; however, a history of lethargy, weight loss and electrolyte abnormalities prompted further investigations. Angiography was postponed, adrenal insufficiency confirmed and steroid replacement commenced. Echocardiography demonstrated reduced left ventricular (LV) function (45%) with regional wall motion abnormalities, although angiography confirmed unobstructed arteries. Steroid replacement induced a rapid improvement in symptoms and LV function. Few cases of TCMP associated with adrenal insufficiency have been reported. This appears to be the first case describing TCMP precipitated by new-onset secondary adrenal insufficiency following long-term steroid use in a male patient, and highlights the importance of considering TCMP in patients presenting with suspected ACS. Here, prompt recognition and treatment of a serious underlying disorder prevented a potentially life-threatening Addisonian crisis.